Preconception care: A Strategy to reduce Neonatal / Child and Maternal Mortality - AbimbolaD, Adewole; Patience O, Odutayo (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
High Neonatal / Child and Maternal mortality still remain an issue of great concern inthe developing countries. These mortalities are as a result of conditions or diseases that arepreventable only if early detection and interventions are done. These interventions that affect themother and child and the family at large can be achieved through adequate Preconception Care.Preconception care is therefore the interventions that aim to identify and modify biomedical,behavioral and social risks to a woman’s health or pregnancy outcome through prevention andmanagement by emphasizing those factors that must be acted on before conception or early inpregnancy to have maximal impact. Its components includes: Health promotion (for example,education and information dissemination), Nutritional planning and supplementation, Screeningand vaccination for diseases known to affect maternal health and pregnancy outcomes and FamilyPlanning. However, majority especially, the adolescences which are the group that is most affectedare not aware of the preconception care and its importance before entering into relationship thatleads to childbearing. This therefore has prompted the review of this topic.